2019
DOI: 10.1177/1367549419861632
|View full text |Cite
|
Sign up to set email alerts
|

Struggling with distinction: How and why people switch between cultural hierarchy and equality

Abstract: In research on cultural taste and distinction, inconsistent and ambivalent attitudes towards hierarchy versus equality have largely been ignored. This study shows, by means of in-depth interviews with 90 Dutch people on their own and others' cultural tastes, that both a hierarchical and an egalitarian repertoire appear in people's narratives, and that these repertoires are often used simultaneously. People still distinguish culturally from others, but not consistently and often reluctantly, as they morally obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Third, both concepts should also be differentiated from hierarchical practices, which still occur in the form of cultural distinction. As previous research showed, many keep distinguishing good from bad tastes (e.g., Holt, 1998;Jarness, 2015;Van den Haak and Wilterdink, 2019). Increased complexity in such distinction processes results in a more complex and diverse cultural hierarchy.…”
Section: Conclusion: a Persistent But More Complex Cultural Hierarchymentioning
confidence: 96%
See 1 more Smart Citation
“…Third, both concepts should also be differentiated from hierarchical practices, which still occur in the form of cultural distinction. As previous research showed, many keep distinguishing good from bad tastes (e.g., Holt, 1998;Jarness, 2015;Van den Haak and Wilterdink, 2019). Increased complexity in such distinction processes results in a more complex and diverse cultural hierarchy.…”
Section: Conclusion: a Persistent But More Complex Cultural Hierarchymentioning
confidence: 96%
“…Kuipers, 2006: 77). Moreover, they often distinguish themselves from higher classes on moral rather than cultural or economic grounds (Lamont, 2000;Van Eijk, 2013;Van den Haak and Wilterdink, 2019).…”
Section: The Interrelation Between Cultural Taste and Hierarchymentioning
confidence: 99%
“…Important historical changes likewise suggest less national or regional specificity. A decline in snobbishness, and hierarchical thinking becoming less justifiable, have been noted by sociologists in countries like the Netherlands and the UK (Kuipers 2013;van den Haak and Wilterdink 2019;van Eijk 2012;Warde 2007). Even the British aristocracy now portrays "ordinariness" in public displays of lifestyle (Friedman and Reeves 2020).…”
Section: Egalitarianismmentioning
confidence: 99%
“…I was careful not to excessively distance myself from my interlocutors, and never introduced myself as a sociologist. 1 Hennion (2007), Benzecry (2012), Whittenburg Ozment (2015 and van den Haak and Wilterdink (2019) have stressed that amateurs are themselves often very much aware of the sociological critique of tastes (Dannefer, 1981), and interviews with sociologists could over-emphasize social concerns (Hennion, 2001). My own amateur practice played an important role: interviews were always discussions between amateurs, supported by 'interesting' wines to taste, and could last for several hours.…”
Section: Studying Amateursmentioning
confidence: 99%